Methods of washing filters in wastewater systems and their effectiveness (Международный научный журнал «Инженер», 2026)
Filters used in industrial enterprises for wastewater treatment have become unusable due to long-term noncompliancewith technical regulations and improper use during operation. This mainly involves the failure towash, replace, and inspect installed filters in a timely manner. This article examines the solution to an effectivemethod for washing filter cartridges. In the first experiment of the study, when the filters were washed with waterat a temperature of 15-20 ºС, the washing time was 16-25 minutes (long term). The solution to the above problemwas the method of increasing the temperature in qualitative laboratory experiments. The results of this methodshow that it is very useful for washing oil and oil products and surfactants remaining in filter cartridges in hightemperaturewater. The reason is that at high temperatures, oil and oil products and surfactants melt and separatefrom the surfaces of filter cartridges, as a result, the washing coefficient of filter cartridges is higher than thewashing coefficient with low-temperature water. It was proven that for the filter loads used in the article, changingthe temperature of the wash water in counterflow conditions from the normal water temperature (15-20 ºС) to ahigher temperature (50-60 ºС) reduces the filter washing time by a factor of 3.